The Effect of the Unified Theory of Acceptance and Use of Technology (UTAUT) Model on User Satisfaction with the Sapawarga App in Bandung - Solihin, Ilham Triananda; Pratminingsih , Sri Astuti (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to analyze the effect of the Unified Theory of Acceptance and Use of Technology (UTAUT) model on user satisfaction with the Sapawarga application in Bandung. The research was motivated by the increasing implementation of digital public services in Indonesia and the need to evaluate user satisfaction as an indicator of the success of e-government services. The study employed a quantitative approach using descriptive and verificative methods. Data were collected through questionnaires distributed to 400 active users of the Sapawarga application in Bandung, selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS version 25. The findings reveal that simultaneously, performance expectancy, effort expectancy, social influence, and facilitating conditions significantly affect user satisfaction. Partially, performance expectancy, effort expectancy, and facilitating conditions have a positive and significant effect on user satisfaction, while social influence does not significantly affect user satisfaction. The results indicate that users are more satisfied when the application provides useful features, ease of use, and adequate supporting facilities. However, several issues—such as system instability, complicated service processes, and limited technical support—still reduce the overall user experience. Therefore, the government and application developers are encouraged to improve system reliability, simplify service procedures, and strengthen technical support to enhance sustainable user satisfaction with digital public services.